2011
DOI: 10.5194/acp-11-8205-2011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the formation of fog and haze in North China Plain (NCP)

Abstract: Abstract. North China Plain (NCP) is one of the most populated and polluted regions in China. During the recent years, haze and fog occur frequently and cause severely low visibility in this region. In order to better understand the impact of aerosol particles on the formation of haze and fog, a long-term record of haze and fog occurrences in the past 56 yr (from 1954-2009) over NCP is analyzed. The results show that there are rapid changes in the occurrences of haze and fog over NCP. The occurrences of haze … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(105 citation statements)
references
References 18 publications
4
101
0
Order By: Relevance
“…A prominent feature in the trends over China is more heterogeneity in the spatial distribution compared to the trend maps over the US and Europe. This could be a result of asynchronous economic development, as several studies reported "lagging" of Vis impairment in rural sites (from ∼ 1990s) compared to urban sites (from ∼ 1960s) in China (Quan et al, 2011;Wu et al, 2012). The overall increasing trend in 1/Vis reverses in the last period of 2006-2013, when most stations in southern China and many in northern China show a statistically significant decreasing trend of 1/Vis.…”
Section: Trend Evaluationmentioning
confidence: 76%
“…A prominent feature in the trends over China is more heterogeneity in the spatial distribution compared to the trend maps over the US and Europe. This could be a result of asynchronous economic development, as several studies reported "lagging" of Vis impairment in rural sites (from ∼ 1990s) compared to urban sites (from ∼ 1960s) in China (Quan et al, 2011;Wu et al, 2012). The overall increasing trend in 1/Vis reverses in the last period of 2006-2013, when most stations in southern China and many in northern China show a statistically significant decreasing trend of 1/Vis.…”
Section: Trend Evaluationmentioning
confidence: 76%
“…This is the main reason for the deterioration of visibility and frequent haze events through light extinction (Cao et al, 2012;Han et al, 2016). During the haze periods, the concentration of particulate matter is much higher than that on normal days, and fine-mode aerosols are predominant (Quan et al, 2011;Zhang and Cao, 2015). Han et al (2016) found that the 71 ± 17 % of PM 10 was PM 2.5 in Beijing and the increasing of PM 2.5 contributed significantly to visibility impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both aerosols and droplets affect visibility (e.g. Elias et al, 2009) and visibility may be reduced below 1 km without droplets but by aerosols (Quan et al, 2011). The event is then called smog (Pearce, 1992) or unactivated fog .…”
Section: Fogmentioning
confidence: 99%
“…Quan et al (2011) showed that haze and mist are usually distinguished according to RH: haze is relatively dry and mist is more humid. Consistently, mist RH at SIRTA was included between 93 % and 100 %, with a monthly average of 99 %.…”
Section: Mistmentioning
confidence: 99%